(untitled) (Psychology Travelogs, 2023)
This article presents the results of research on the role of reflection in shaping harmonious and mutually understanding relationships within a team. The essence of the concept of reflection is defined as a property of a person’s thinking, which directs a person to understand and realize the forms of consciousness inherent in him for the purpose of analyzing his own activity, self-knowledge, which characterizes the peculiarities of his spiritual world. Based on the characterization of types of "reflection in communication" (social-perceptual, communicative, socio-psychological) manifestations of reflection in team relationships are analyzed. The stages of team reflection are considered, adherence to which helps the team identify strengths and weaknesses in their activities, ensure effective cooperation to achieve common goals, and improve relationships. Several tools and methods for conducting reflection that contribute to the formation of harmonious relationships within a team are discussed: the Scrum methodology, the Six Thinking Hats techniques, debriefing. Highlighted as methods addressing this task are the "Traffic Light", "Brainstorming", "Positive Insights", "Achievement Portfolio", "Dialogic Circles". Conclusions are drawn that reflection is an integral component of the effectiveness of a team built on positive relationships, allowing for better understanding of each other, communication patterns, reducing the risk of misunderstandings and conflicts in interpersonal communication, promoting mutual understanding and the development of harmonious relationships. It is emphasized that open discussions of individual thoughts, impressions, and shortcomings help build trust among team members, create a conducive environment for interaction, cooperation, and support. It is stressed that as a result of reflection, each team member has the opportunity to create their own self-improvement program, incorporating directions related to the development of humane qualities and the ability to build relationships with colleagues on a positive basis.